Deficit of resolution receptor magnifies inflammatory leukocyte directed cardiorenal and endothelial dysfunction with signs of cardiomyopathy of obesity. Issue 8 (16th June 2020) - Tourki, Bochra; Kain, Vasundhara; Shaikh, Saame Raza; Leroy, Xavier; Serhan, Charles N.; Halade, Ganesh V.
Abstract: Chronic unresolved inflammation is the primary determinant of cardiovascular disease. Precise mechanisms that define the genesis of unresolved inflammation in heart failure with preserved ejection fraction (HFpEF) are of interest due to the obesity epidemic. To examine the obesity phenotype and its direct/indirect consequences, multiple approaches were employed using the lipoxin receptor (abbreviated as ALX) dysfunction mouse model. Indirect calorimetry analyses revealed that the deletion of ALX dysregulated energy metabolism driving toward age‐related obesity. Heart function data suggest that obesity‐prone ALX deficient mice had impaired myocardium strain. Comprehensive measurement of chemokines, extracellular matrix, and arrhythmogenic arrays confirmed the dysregulation of multiple ion channels gene expression with amplified inflammatory chemokines and cytokines response at the age of 4 months compared with WT counterparts. Quantitative analyses of leukocytes demonstrated an increase of proinflammatory Ly6C hi CCR2 + macrophages in the spleen and heart at a steady‐state resulting in an inflamed splenocardiac axis. Signs of subtle inflammation were marked with cardiorenal, endothelial defects with decreased CD31 and eNOS and an increased iNOS and COX2 expression. Thus, ALX receptor deficiency serves as an experimental model that defines multiple cellular and molecular mechanisms in HFpEF that could be a target for the development of HFpEF therapy in cardiovascular medicine.